Seroprevalence of bluetongue infection among ruminant livestock in Peninsular Malaysia - Roshaslinda D. (2024)
Bluetongue (BT) is an arthropod-borne viral disease of domestic and wild ruminants caused by Bluetongue virus (BTV). It has been reported in most tropical and subtropical regions of the world which raises significant socioeconomic concerns for international trade in animals and animal products. However, recent and updated information related to the current prevalence of BT in Malaysia is limited. The last holistic report was reported during BT outbreaks in the year of 1990s. This study aims to determine the current status of seroprevalence of BT among ruminants in Malaysia from 2013 to 2019. A total of 9,787 serum samples from buffalo, cattle, deer, goat as well as sheep were received from January 2013 until December 2019. All these serum samples were subjected to Agar Gel Immunodiffusion (AGID) test to detect the presence of antibodies towards BTV. The overall status of BTV was 20.18 % (1,975/9,787), with 56 % (14/25) in deer, 46.4 % (428/922) in cattle and 35.7 % (60/168) in buffalo. Positive BT antibodies were detected in young animals (<6 months) with 30.60 %, while 23.61 % in adult animals (>2 years). The results of this study revealed that BTV is still circulating at low level in domestic and wild ruminant livestock animals in Malaysia. It is suggested that this disease needs close monitoring to prevent possible outbreaks in the future.